Email is evil! Behavioural responses towards permission-based direct email marketing and gender differences - Mahmoud, A. B.; Grigoriou, N.; Fuxman, L.; Hack-Polay, D.; Mahmoud, F. B.; Yafi, E.; Tehseen, Shehnaz * (Emerald, 2019)
Purpose: This study aims to assess consumers’ beliefs in three Middle Eastern Arab countries regarding attitudinal and behavioural responses towards permission-based direct email marketing (hereafter DEM) and the moderating role of gender in the hypothesised path model. Design/methodology/approach: Structural equation modelling was used to test the hypothesised path model by using data collected from 829 respondents. Findings: The findings show that attitude was found to fully mediate the relationship between beliefs and behavioural responses towards permission-based DEM. Gender moderates the relationship between beliefs and attitudes and responses to permission-based DEM. Notably, female respondents were found to react more actively when exposed to permission-based DEM. Research limitations/implications: Further qualitative research is needed to learn more about how and why individuals develop behavioural intentions in certain ways towards opt-in DEM. In addition, neuropsychology approaches such as eye-tracking are endorsed for future research to gain more insights and conquer biases associated with self-reporting procedures in countries where such technologies are deemed as legal and ethical to be used with human subjects. Practical implications: Advertisers promoting products and services in the Middle Eastern Arab context should take further steps to enhance the quality of information (including cultural sensitiveness) and the perceived entertainment value that could be delivered to consumers through permission-based DEM, especially for female internet users. Additionally, this study highly recommends the double opt-in approach to permission-based DEM. Originality/value: To the best of the authors’ knowledge, this is the first attempt to address the gender role as a moderator of the path depicting the effectiveness of permission-based DEM approach in the Middle East (Arab counties) from beliefs to behavioural responses via attitudes.